Analisis Penentuan Harga Pokok Produksi dengan Metode Activity-Based Costing sebagai Dasar Penetapan Harga Jual pada UMKM Himalayan Coffee - Khairulla, Salma; Lasmini, Lilis; Ardiansyah, Hendri Nur (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
MSMEs have a strategic role in the Indonesian economy, including in the culinary sector which is experiencing rapid growth, especially in Karawang Regency. However, this growth has led to intense competition among café businesses. One important factor in business sustainability is determining an accurate Cost of Goods Manufactured (COGS) as the basis for a selling price strategy. Himalayan Coffee, an MSME cafe in Karawang, still uses traditional methods in calculating COGS that do not reflect actual costs, resulting in undercosting and overcosting conditions in several products. This study aims to examine the application of Activity-Based Costing (ABC) in the calculation of COGS at Himalayan Coffee to improve cost accuracy and support more competitive selling price decision making. This research method is a qualitative method of case study approach with in-depth interview techniques and direct observation as primary data, and financial reports as secondary data. The results showed that the application of ABC resulted in a more accurate COGS than the traditional method, with condition values on Himalayan Latte (undercost), Americano (undercost), and Cireng, Chocolate Cheese Toast and Crispy Banana (overcost) products. Profit analysis showed a change in profit margin of up to 18% in some products. With the application of ABC, Himalayan Coffee can set selling prices more precisely, determine product strategies, and improve cost efficiency.